2008
DOI: 10.1074/jbc.m708968200
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Myostatin on Adipogenic Differentiation of Human Bone Marrow-derived Mesenchymal Stem Cells Are Mediated through Cross-communication between Smad3 and Wnt/β-Catenin Signaling Pathways

Abstract: The effects of myostatin on adipogenic differentiation are poorly understood, and the underlying mechanisms are unknown. We determined the effects of human recombinant myostatin protein on adipogenesis of bone marrow-derived human mesenchymal stem cells (hMSCs) and adipose tissuederived preadipocytes. For both progenitor cell types, differentiation in the presence of myostatin caused a dose-dependent reduction of lipid accumulation and diminished incorporation of exogenous fatty acid into cellular lipids. Myos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
80
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(83 citation statements)
references
References 58 publications
1
80
0
2
Order By: Relevance
“…Myostatin was recently reported to in-hibit myogenesis and promote adipogenesis [15], and was able to substitute for dexamethasone in inducing adipogenic differentiation of mouse mesenchymal stem cells (MSCs) in vitro [16]. Nevertheless, inconsistent results have been reported in primary human bone marrow MSCs [17]. Despite this, it has been suggested that myostatin is involved in fat deposition and modulation of adipogenic differentiation.…”
mentioning
confidence: 88%
“…Myostatin was recently reported to in-hibit myogenesis and promote adipogenesis [15], and was able to substitute for dexamethasone in inducing adipogenic differentiation of mouse mesenchymal stem cells (MSCs) in vitro [16]. Nevertheless, inconsistent results have been reported in primary human bone marrow MSCs [17]. Despite this, it has been suggested that myostatin is involved in fat deposition and modulation of adipogenic differentiation.…”
mentioning
confidence: 88%
“…Wnt inhibits both brown and white adipogenesis by blocking the induction of key transcription factors for adipogenesis (PPARg and C/EBPa in WAT and PGC1a in BAT (Seale et al, 2009)). Myostatin inhibits white adipogenesis through the activation of Wnt signalling, which in turn inhibits the expression of PPARg in human MSC and primary white pre-adipocytes (Guo et al, 2008). Conversely, myostatin promotes the commitment and differentiation of multi-potent mesenchymal cells lines into the adipogenic lineage and inhibits their differentiation into the myogenic lineage (Artaza et al, 2005).…”
Section: Molecular Control Of the Cell Lineage Fatementioning
confidence: 99%
“…These morphological abnormalities are more severe in homozygous Gdf8 2/2 mice, consistent with the role of Gdf8 in bone development (Hamrick et al, 2007;Kellum et al, 2009). The mechanisms by which myostatin regulates bone formation are not well understood, but it is clear that myostatin has direct effects on the proliferation and differentiation of mesenchymal stem cells (Rebbapragada et al, 2003;Artaza et al, 2005;Guo et al, 2008). Our new mouse models might help to unravel the exact role of myostatin in regulating osteogenesis.…”
Section: Discussionmentioning
confidence: 60%